ICF Linking and Cognitive Interviewing Are Complementary Methods for Optimizing Content Validity of Outcome Measures: An Integrated Methods Review - MacDermid, Joy C. (Frontiers in Rehabilitation Sciences, 2021)
Content validity is a fundamental requirement of outcome measures. After reviewing operational needs and existing definitions, content validity weas defined as: the extent to which a measure provides a comprehensive and true assessment of the key relevant elements of a specified construct or attribute across a defined range, clearly and equitably for a stated target audience and context. ICF linkage rules from 2002, 2005 and 2019 have provide increasingly clear processes for describing and evaluating content of outcome measures. ICF Core Sets provide international reference standards of the core constructs of importance for different health conditions. Both are important as reference standards during content validation. To summarize their use as reference standards, the following summary indicators were proposed: 1) Measure to ICF linkage, 2) Measure to (Brief or Comprehensive) Core Set Absolute Linkage, 3)Measure to (Brief or Comprehensive) Core Set Unique Linkage, 4) Core Set Representation, and 5) Core Set Unique Disability Representation. Methods to assess how respondents engage with content are needed to complement ICF-linking. Cognitive interviewing is an ideal method since it explored how respondents interpret and calibrate response to individual items on an outcome measure. We proposed a framework for classifying these responses: Clarity/Comprehension, Relevance, Inadequate response definition, Reference Point, Perspective modification, and Calibration Across Items. A scoping review of XX manuscripts using ICF linking for content validation since updated linking rules were published in 2016, found that typically linking was used to validate existing measures, involved multiple raters, used 2005 linking rules, summarized content at a concept level (e.g., impairment, activity, participation) and/or use core sets as a reference standard. Infrequently, ICF linking was used to create item pools/conceptual frameworks for new measures, applied the full scope of the 2019 rules, used summary indicators, or integrated ICF-linking with qualitative methods like cognitive interviews. We conclude that ICF linkage is a powerful tool for content validity during development or validation of PROM. Best practices include use of updated ICF linking rules, triangulation with participant assessments of clarity and relevance preferably obtained using cognitive interview methods, and application of defined summary indicators.